Embellish Kitchen Design / Norliana Baharil ... [et al.] - Baharil, Norliana; Ramli, Risya Raheeda; Mohamad Kasim, Suzila; Mohd Taib, Normaisarah (Faculty of Information Management, 2004)
We have agreed to choose Embellish Kitchen Design as the name of our business. Embellish Kitchen Design means our business's innovation inline with an up to date design. We think that the mention name is suitable for our goals as well as to give the spirit in running the business. Embellish Kitchen Design is a partnership type of business. We choose this concept because partners as such run this type of business they share the amount of capital, profit and lost. The advantages of it are any loses are divided into the number of share holders. Moreover, the sum of money to be paid base on the shareholders equity.